2011
DOI: 10.1002/mnfr.201100481
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and risk assessment of acrolein in food

Abstract: Acrolein is an α,β-unsaturated aldehyde formed by thermal treatment of animal and vegetable fats, carbohydrates and amino acids. In addition it is generated endogenously. As an electrophile, acrolein forms adducts with gluthathione and other cellular components and is therefore cytotoxic. Mutagenicity was shown in some in vitro tests. Acrolein forms different DNA adducts in vivo, but mutagenic and cancerogenous effects have not been demonstrated for oral exposure. In subchronic oral studies, local lesions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
127
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 98 publications
1
127
1
4
Order By: Relevance
“…While other qualitative research has found that women living at high risk tend to be either making lifestyle or health care adjustments to reduce risk [21,35,36], we have found a greater range of risk management styles in our study, including those who do not know why they 'don't do anything.' The greater range of responses to risk revealed here is likely to be due to the fact that we were able to recruit outside the more motivated clinic-based sample to include women who were managing their familial breast cancer risk without the support of specialists, or genetic counselling or testing.…”
Section: Resultscontrasting
confidence: 80%
See 3 more Smart Citations
“…While other qualitative research has found that women living at high risk tend to be either making lifestyle or health care adjustments to reduce risk [21,35,36], we have found a greater range of risk management styles in our study, including those who do not know why they 'don't do anything.' The greater range of responses to risk revealed here is likely to be due to the fact that we were able to recruit outside the more motivated clinic-based sample to include women who were managing their familial breast cancer risk without the support of specialists, or genetic counselling or testing.…”
Section: Resultscontrasting
confidence: 80%
“…While there is agreement that understanding risk perception is an essential task if we are to assist women to manage risk, and make an informed decision about screening and prevention practices [19], there is also agreement that we currently do not have a consensus on effective ways to measure risk perception [7-9]. Risk is more complicated than many of the instruments developed to measure objective risk perception are able to capture, as people perceive risk in the context of their day-to-day lives, within their families, using the evidence they have been provided with, and the everyday reasoning tools available to them [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Due to the noninvasive nature of measuring 3-HPMA in urine, this method has been used in estimating acrolein intake through tobacco exposure and food consumption in humans. 11,12,15 Based on this method, it was revealed that acrolein is significantly elevated in smokers as compared to nonsmokers, and decreased following the cessation of cigarette smoke. 11 However, such a method has not been widely used in human and animals models in which endogenous acrolein are elevated due to central nervous system damage or disease.…”
Section: Introductionmentioning
confidence: 99%